2021
DOI: 10.1101/2021.10.04.462784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ptbp1 deletion does not induce glia-to-neuron conversion in adult mouse retina and brain

Abstract: Somatic reprogramming of glia into neurons is a potentially promising approach for the replacement of neurons lost to injury or neurodegenerative disorders. Knockdown of the polypyrimidine tract-binding protein Ptbp1 has been recently reported to induce efficient conversion of retinal Mϋller glia and brain astrocytes into functional neurons. However, genetic analysis of Ptbp1 function in adult glia has not been conducted. Here, we use a combination of genetic lineage tracing, scRNA-Seq, and electrophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…This could reflect the action of cis-regulatory elements that bind transcription factors that promote neuronal-specific expression, the activity of the vector-encoded transcription factors on the GFAP minipromoter, or some combination of the two. Similar conclusions have been drawn following re-examination of claims of astrocyte-to-neuron conversion in brain (Chen et al, 2021;Hoang et al, 2021;Wang et al, 2021a), and these findings raise serious concerns about the accuracy of previously reported claims of AAV-mediated Müller glia-to-neuron conversion (Yao et al, 2018;Zhou et al, 2020;Xiao et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…This could reflect the action of cis-regulatory elements that bind transcription factors that promote neuronal-specific expression, the activity of the vector-encoded transcription factors on the GFAP minipromoter, or some combination of the two. Similar conclusions have been drawn following re-examination of claims of astrocyte-to-neuron conversion in brain (Chen et al, 2021;Hoang et al, 2021;Wang et al, 2021a), and these findings raise serious concerns about the accuracy of previously reported claims of AAV-mediated Müller glia-to-neuron conversion (Yao et al, 2018;Zhou et al, 2020;Xiao et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…Aldh1l1-CreER T2 ;LSL-YFP transgenic mouse lines exhibit high specificity in astrocyte, with relatively low (4.3%) neuron mislabeling 6,11 . Indeed, three independent groups observed no AtN conversion through Ptbp1 knockdown or knockout in vivo using Aldh1l1-CreER T2 labeling systems 4,6,7 . In contrast, in another common astrocyte labeling systems using GFAP promoter, AtN conversion have been able to occur .…”
Section: Discussionmentioning
confidence: 99%
“…Since the Aldh1l1-CreER T2 ;LSL-YFP transgenic mouse lines exhibit high specificity in astrocyte, with relatively low (4.3%) neuron mislabeling, it is more specific than GFAP promoter 6,13 . Indeed, three independent groups using Aldh1l1-CreER T2 labeling systems and observed no AtN conversion through Ptbp1 knockdown or knockout in vivo 4,6,7 . However, application of an endogenous promoter-driven mGFAP-Cre;LSL-YFP mouse strain enabled stringent, astrocyte-specific YFP expression, which also showed no AtN conversion under Ptbp1 knockdown 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Ptbp1 deletion did not make astrocytes trigger any neuron-like potentials, suggesting that their electrophysiological functions were not altered. In addition, by detecting the expression of glia-specific markers, researchers found that Ptbp1-deficient Müller glia retained expression of the glial marker SOX9 and did not detect gene expression characteristic of neurons, indicating that loss of Ptbp1 function did not significantly alter gene expression in Müller glia nor cause these cells to lose their identity ( Hoang et al, 2021 ).…”
Section: Astrocyte Reprogramming Through Trans-differentiationmentioning
confidence: 99%
“…Secondly, previous study stated that knocking down Ptbp1 readily converted glial cells into neurons in young mice but was difficult to achieve in older mice ( Qian et al, 2020 ). On the contrary, the study recently posted in bioRxiv website showing that Ptbp1 deletion does not induce trans-differentiation of astrocytes into neurons in adult mouse retina and brain ( Hoang et al, 2021 ). Controversies in this field have not yet been definitively resolved, suggesting that we should use more rigorous genetic tools in the future to validate the report on the glial-to-neuron reprogramming.…”
Section: Conclusion and Perspectivementioning
confidence: 99%